Strong-oxidizing-property acid water heat treatment coal derived hard carbon negative electrode material as well as preparation and application thereof
Through oxidative acid hydrothermal treatment technology, the coal is structurally regulated and a uniform and dense sodium storage active site is constructed, which solves the problem of low sodium storage performance of hard carbon anode materials of sodium ion batteries, and significantly improves the sodium storage performance of coal-based hard carbon.
Patent Information
- Application Number
- CN202510098008.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-04-25
AI Technical Summary
The existing hard carbon anode materials for sodium ion batteries have bottleneck problems such as low reversible sodium storage capacity and low Coulomb efficiency for the first time, especially coal-based hard carbon materials are difficult to build uniform and dense sodium storage active sites.
The oxidative acid hydrothermal treatment technology is adopted to construct a uniform and dense sodium storage active site in coal-derived hard carbon by performing medium-low temperature pyrolysis, crushing and hydrothermal reaction of coal, combined with high-temperature carbonization.
The sodium storage performance of coal-based hard carbon in sodium ion batteries has been significantly improved, with the first charging capacity reaching 342.2mAh g-1, the first discharge capacity reaches 417.7mAh g-1, and the first Coulomb efficiency reaches 86.0%.
Smart Images

Figure HDA0005253380250000011 
Figure HDA0005253380250000012 
Figure HDA0005253380250000021
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a hard carbon negative electrode material derived from coal subjected to strong oxidizing acid hydrothermal treatment, and a preparation method and application thereof. Background Art
[0002] Sodium-ion batteries (SIBs) have attracted extensive attention in the field of large-scale energy storage due to their advantages such as low cost, abundant sodium resources, and physical and chemical properties with lithium. The commercial application of SIBs is limited by the lack of high-performance, low-cost, and scalable anode materials. Among the anode materials of sodium-ion batteries, oxides, alloys, phosphides, and organic anode materials have problems such as high irreversible capacity, high redox potential, and poor cycle performance involving phase change. In contrast, hard carbon materials have short-range carbon crystallites and large interlayer spacing. The sodium ion intercalation of graphite crystallites and the deposition of sodium ions in closed pores formed by crystallite stacking are the main mechanisms contributing to the storage of low-potential sodium ions. However, there is currently a lack of hard carbon anode materials for sodium-ion batteries with high sodium storage performance, low cost, and scalable preparation.
[0003] Scalable hard carbon precursors can be divided into three categories: biomass, oxygen-containing resins, and fossil fuels (coal, asphalt, etc.). Compared with other precursors, coal has the characteristics of abundant reserves, low price, and high carbon content, and is one of the ideal precursors for low-cost hard carbon negative electrodes for sodium-ion batteries. However, coal has the characteristics of high carbon content, high degree of aromatic ring condensation, and dense internal structure, making it difficult to construct uniform and dense sodium storage active sites in coal-based hard carbon blocks. Therefore, coal-based hard carbon has bottleneck problems such as low reversible sodium storage capacity and low first coulomb efficiency. Summary of the invention
[0004] In view of the problem that the coal precursor has a dense structure and it is difficult to construct uniform and dense sodium storage sites in coal-based hard carbon, the primary purpose of the present invention is to provide a method for preparing a hard carbon negative electrode material derived from coal by strong oxidizing acid hydrothermal treatment.
[0005] The present invention adopts the structural control strategy of oxidative acid hydrothermal to construct uniform and dense sodium storage active sites in coal-derived hard carbon. The prepared coal-based hard carbon material has a capacity of 342.2 mAh g -1 First charge capacity, 417.7mAh g -1 The first discharge capacity and the first coulombic efficiency of 86.0% significantly improved the sodium storage performance of coal-based hard carbon for sodium-ion batteries.
[0006] Another object of the present invention is to provide a strong oxidizing acid hydrothermal treatment coal-derived hard carbon negative electrode material obtained by the above preparation method.
[0007] Another object of the present invention is to provide the application of the above-mentioned strongly oxidizing acid hydrothermal treated coal-derived hard carbon negative electrode material in sodium ion batteries.
[0008] The purpose of the present invention is achieved through the following technical solutions:
[0009] A method for preparing a hard carbon negative electrode material derived from coal subjected to strong oxidizing acid hydrothermal treatment, comprising the following steps:
[0010] (1) pyrolyzing coal at low temperature under an inert atmosphere to obtain semi-coke;
[0011] (2) crushing the semi-coke, mixing it with an oxidizing acid solution, performing a hydrothermal reaction, washing, and drying to obtain an acid-heat-treated carbon intermediate;
[0012] (3) The acid-heat-treated carbon intermediate is carbonized at high temperature in an inert atmosphere to obtain a strongly oxidizing acid-hydrothermal-treated coal-derived hard carbon negative electrode material.
[0013] Preferably, the coal in step (1) is at least one of bituminous coal and lignite; more preferably lignite.
[0014] Preferably, the inert atmosphere in step (1) is at least one of nitrogen, helium and argon.
[0015] Preferably, the pyrolysis temperature in step (1) is 200-900°C; more preferably 600-700°C.
[0016] Preferably, the pyrolysis time in step (1) is 0.5-10 h; more preferably 1-2 h.
[0017] Preferably, the semi-coke in step (2) is crushed to 10-500 mesh; more preferably 50-300 mesh; the crushing method is at least one of mechanical ball milling, grinding and air flow grinding; more preferably at least one of grinding and air flow grinding.
[0018] Preferably, the oxidizing acid in the oxidizing acid solution in step (2) is at least one of sulfuric acid, permanganic acid, dichromic acid, hypochlorous acid, chloric acid, chlorous acid, perchloric acid, nitrous acid and nitric acid.
[0019] Preferably, the concentration of the oxidizing acid solution in step (2) is 30-63 wt. %; more preferably 30-50 wt. %; most preferably 30-40 wt. %.
[0020] Preferably, the temperature of the hydrothermal reaction in step (2) is 50-300°C; more preferably 80-120°C.
[0021] Preferably, the hydrothermal reaction time in step (2) is 1-36 h; more preferably 1-2 h.
[0022] Preferably, the washing in step (2) refers to washing with water until neutral.
[0023] Preferably, the inert atmosphere in step (3) is at least one of nitrogen, helium and argon.
[0024] Preferably, the carbonization temperature in step (3) is 900-1800°C; more preferably 1100-1300°C; most preferably 1200-1300°C.
[0025] Preferably, the carbonization time in step (3) is 1-10 h; more preferably 1-2 h.
[0026] The invention provides a hard carbon negative electrode material derived from coal subjected to strong oxidizing acid hydrothermal treatment; the material is prepared by the above-mentioned preparation method.
[0027] The present invention provides the use of the above-mentioned strong oxidizing acid hydrothermal treatment coal-derived hard carbon negative electrode material in a sodium ion battery.
[0028] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0029] (1) The present invention first performs medium-low temperature pyrolysis on the coal raw material to preliminarily loosen the dense internal structure of the coal; then uses a strong oxidizing acid solution to perform hydrothermal corrosion oxidation to further regulate the internal structure of the semi-coke; and finally performs high-temperature carbonization to construct uniform and dense sodium storage active sites in the coal-derived hard carbon, thereby improving the sodium storage performance of the coal hard carbon.
[0030] (2) The coal-based hard carbon material obtained by the present invention has a capacity of 342.2 mAh g -1 First charge capacity, 417.7mAh g -1 The first discharge capacity and the first coulombic efficiency of 86.0% significantly improved the sodium storage performance of coal-based hard carbon for sodium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a scanning electron microscope image of coal-based hard carbon prepared by a hydrothermal method using 20% by mass nitric acid in comparative example 1 of the present invention.
[0032] Figure 2 This is a scanning electron microscope image of coal-based hard carbon prepared by a hydrothermal method using 30% by mass nitric acid in Example 1 of the present invention.
[0033] Figure 3 This is a scanning electron microscope image of coal-based hard carbon prepared by a hydrothermal method using 40% by mass nitric acid in Example 2 of the present invention.
[0034] Figure 4The charge and discharge curves of the hard carbon materials obtained by pyrolysis of nitric acid at 1200°C after hydrothermal treatment at different mass fractions prepared in Comparative Example 1 and Examples 1 and 2 of the present invention in a sodium ion half-cell.
[0035] Figure 5 The charge and discharge curves of the hard carbon materials prepared at different carbonization temperatures in sodium ion half cells after hydrothermal treatment with 30% by mass nitric acid in Examples 1, 3 and 4 of the present invention.
[0036] Figure 6 The charge and discharge curves of the hard carbon materials in sodium ion half-cells obtained by hydroheating coals of different ranks with 30% nitric acid in Examples 1 and 5 of the present invention and Comparative Example 2.
[0037] Figure 7 The charge and discharge curves of the low-rank coal-derived hard carbon material in the sodium ion half-cell obtained by changing the pulverization method after hydrothermal treatment with 30% nitric acid in Examples 1, 6 and 7 of the present invention. DETAILED DESCRIPTION
[0038] The present invention is further described in detail below in conjunction with examples and drawings, but the embodiments of the present invention are not limited thereto.
[0039] If no specific conditions are specified in the examples of the present invention, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. All raw materials, reagents, etc., whose manufacturers are not specified, are conventional products that can be purchased commercially.
[0040] Comparative Example 1
[0041] a. Place lignite in a tubular furnace and pyrolyze it at 600℃ for 2h under nitrogen atmosphere to obtain semi-coke.
[0042] b. Grind the semi-coke obtained in step a, take a 50-mesh product and place it on the inner lining of a hydrothermal kettle, add a 20 wt.% nitric acid solution (corresponding to a molar concentration of 3.53 mol / L), and hydroheat at 80°C for 2 h to obtain an oxidative acid-treated carbon intermediate.
[0043] c. The oxidative acid-treated carbon intermediate obtained in step b is washed with water until it is neutral, dried at 80° C., and then carbonized at 1200° C. for 2 h in a nitrogen atmosphere to obtain a coal-derived hard carbon material.
[0044] Example 1
[0045] a. Place lignite in a tubular furnace and pyrolyze it at 600℃ for 2h under nitrogen atmosphere to obtain semi-coke.
[0046] b. Grind the semi-coke obtained in step a, take a 50-mesh product and place it on the inner lining of a hydrothermal kettle, add a 30 wt.% nitric acid solution and hydroheat at 80°C for 2 h to obtain an oxidative acid-treated carbon intermediate.
[0047] c. The oxidative acid-treated carbon intermediate obtained in step b is washed with water until it is neutral, dried at 80° C., and then carbonized at 1200° C. for 2 h in a nitrogen atmosphere to obtain a coal-derived hard carbon material.
[0048] Example 2
[0049] a. Place lignite in a tubular furnace and pyrolyze it at 600℃ for 2h under nitrogen atmosphere to obtain semi-coke.
[0050] b. Grind the semi-coke obtained in step a, take a 50-mesh product and place it on the inner lining of a hydrothermal kettle, add a 40 wt.% nitric acid solution and hydroheat at 80°C for 2 h to obtain an oxidative acid-treated carbon intermediate.
[0051] c. The oxidative acid-treated carbon intermediate obtained in step b is washed with water until it is neutral, dried at 80° C., and then carbonized at 1200° C. for 2 h in a nitrogen atmosphere to obtain a coal-derived hard carbon material.
[0052] Example 3
[0053] a. Place lignite in a tubular furnace and pyrolyze it at 600℃ for 2h under nitrogen atmosphere to obtain semi-coke.
[0054] b. Grind the semi-coke obtained in step a, take a 50-mesh product and place it on the inner lining of a hydrothermal kettle, add a 30 wt.% nitric acid solution and hydroheat at 80°C for 2 h to obtain an oxidative acid-treated carbon intermediate.
[0055] c. The oxidative acid-treated carbon intermediate obtained in step b is washed with water until it is neutral, dried at 80° C., and then carbonized at 1100° C. for 2 h in a nitrogen atmosphere to obtain a coal-derived hard carbon material.
[0056] Example 4
[0057] a. Place lignite in a tubular furnace and pyrolyze it at 600℃ for 2h under nitrogen atmosphere to obtain semi-coke.
[0058] b. Grind the semi-coke obtained in step a, take a 50-mesh product and place it on the inner lining of a hydrothermal kettle, add a 30 wt.% nitric acid solution and hydroheat at 80°C for 2 h to obtain an oxidative acid-treated carbon intermediate.
[0059] c. The oxidative acid-treated carbon intermediate obtained in step b is washed with water until it is neutral, dried at 80° C., and then carbonized at 1300° C. for 2 h in a nitrogen atmosphere to obtain a coal-derived hard carbon material.
[0060] Comparative Example 2
[0061] a. Place anthracite in a tubular furnace and pyrolyze it at 600℃ for 2h under nitrogen atmosphere to obtain semi-coke.
[0062] b. Grind the semi-coke obtained in step a, take a 50-mesh product and place it on the inner lining of a hydrothermal kettle, add a 30 wt.% nitric acid solution and hydroheat at 80°C for 2 h to obtain an oxidative acid-treated carbon intermediate.
[0063] c. The oxidative acid-treated carbon intermediate obtained in step b is washed with water until it is neutral, dried at 80° C., and then carbonized at 1200° C. for 2 h in a nitrogen atmosphere to obtain a coal-derived hard carbon material.
[0064] Example 5
[0065] a. Place bituminous coal in a tubular furnace and pyrolyze it at 600℃ for 2h under nitrogen atmosphere to obtain semi-coke.
[0066] b. Grind the coal block obtained in step a, take 50 mesh coal and put it into the lining of the hydrothermal kettle, add 30wt.% nitric acid solution and hydroheat at 80℃ for 2h to obtain an oxidative acid-treated carbon intermediate.
[0067] c. The oxidative acid-treated carbon intermediate obtained in step b is washed with water until it is neutral, dried at 80° C., and then carbonized at 1200° C. for 2 h in a nitrogen atmosphere to obtain a coal-derived hard carbon material.
[0068] Example 6
[0069] a. Place lignite in a tubular furnace and pyrolyze it at 600℃ for 2h under nitrogen atmosphere to obtain semi-coke.
[0070] b. The semi-coke obtained in step a is subjected to air flow pulverization, and a 50-mesh product is taken and placed in the inner lining of a hydrothermal kettle. A 30 wt.% nitric acid solution is added and hydrothermaled at 80° C. for 2 h to obtain an oxidative acid-treated carbon intermediate.
[0071] c. The oxidative acid-treated carbon intermediate obtained in step b is washed with water until it is neutral, dried at 80° C., and then carbonized at 1200° C. for 2 h in a nitrogen atmosphere to obtain a coal-derived hard carbon material.
[0072] Example 7
[0073] a. Place lignite in a tubular furnace and pyrolyze it at 600℃ for 2h under nitrogen atmosphere to obtain semi-coke.
[0074] b. The semi-coke obtained in step a is subjected to mechanical ball milling, and a 50-mesh product is taken and placed in the inner lining of a hydrothermal kettle. A 30 wt.% nitric acid solution is added and hydrothermaled at 80° C. for 2 h to obtain an oxidative acid-treated carbon intermediate.
[0075] c. The oxidative acid-treated carbon intermediate obtained in step b is washed with water until it is neutral, dried at 80° C., and then carbonized at 1200° C. for 2 h in a nitrogen atmosphere to obtain a coal-derived hard carbon material.
[0076] The coal-derived hard carbon material prepared in the embodiment is used as the negative electrode material, which is ground and sieved; the sieved powder is slurried, coated on the current collector, dried, punched, and assembled and tested for the sodium ion battery.
[0077] The electrode size is 14 mm in diameter and the loading capacity is 1.5-2 mg cm -3 The test conditions are 20mAg -1 Current density, cut-off voltage is 0.001-2.5V (vs.Na / Na + ) under constant current charge and discharge curve test of sodium ion half-cell.
[0078] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a hard carbon negative electrode material derived from coal subjected to strong oxidizing acid hydrothermal treatment, characterized in that: The following steps are involved: (1) pyrolyzing coal at 200-900°C under an inert atmosphere to obtain semi-coke; (2) crushing the semi-coke, mixing it with an oxidizing acid solution, performing a hydrothermal reaction, washing, and drying to obtain an acid-heat-treated carbon intermediate; (3) The acid-heat-treated carbon intermediate is carbonized at 900-1800° C. in an inert atmosphere to obtain a strongly oxidizing acid-hydrothermal-treated coal-derived hard carbon negative electrode material.
2. The method for preparing a hard carbon negative electrode material derived from strongly oxidizing acid hydrothermal treatment of coal according to claim 1, characterized in that: The oxidizing acid in the oxidizing acid solution of step (2) is at least one of sulfuric acid, permanganic acid, dichromic acid, hypochlorous acid, chloric acid, chlorous acid, perchloric acid, nitrous acid and nitric acid; and / or, the concentration of the oxidizing acid solution in step (2) is 30-63 wt.%; And / or, the temperature of the hydrothermal reaction in step (2) is 50-300° C.; And / or, the time of the hydrothermal reaction in step (2) is 1-36h.
3. The method for preparing a hard carbon negative electrode material derived from strongly oxidizing acid hydrothermal treatment of coal according to claim 1 or 2, characterized in that: The carbonization time in step (3) is 1-10h; And / or, the inert atmosphere in step (3) is at least one of nitrogen, helium and argon.
4. The method for preparing a hard carbon negative electrode material derived from strongly oxidizing acid hydrothermal treatment of coal according to claim 1 or 2, characterized in that: The coal in step (1) is at least one of anthracite and lignite; And / or, the semi-coke in step (2) is crushed to 10-500 mesh; And / or, the pulverizing method in step (2) is at least one of mechanical ball milling, grinding and air flow pulverizing.
5. The method for preparing a hard carbon negative electrode material derived from strongly oxidizing acid hydrothermal treatment of coal according to claim 1 or 2, characterized in that: The pyrolysis temperature in step (1) is 600-700°C; And / or, the pyrolysis time in step (1) is 0.5-10h; And / or, the inert atmosphere in step (1) is at least one of nitrogen, helium and argon.
6. The method for preparing a hard carbon negative electrode material derived from strongly oxidizing acid hydrothermal treatment of coal according to claim 1 or 2, characterized in that: The concentration of the oxidizing acid solution in step (2) is 30-50wt.% or 30-40wt.%; And / or, the temperature of the hydrothermal reaction in step (2) is 80-120°C; And / or, the hydrothermal reaction time in step (2) is 1-2h.
7. The method for preparing a hard carbon negative electrode material derived from strongly oxidizing acid hydrothermal treatment of coal according to claim 1, characterized in that: The carbonization temperature in step (3) is 1100-1300° C. or 1200-1300° C.; And / or, the carbonization time in step (3) is 1-2h.
8. The method for preparing a hard carbon negative electrode material derived from strongly oxidizing acid hydrothermal treatment of coal according to claim 1, characterized in that: The semi-coke in step (2) is crushed to 50-300 mesh; And / or, the pulverizing method in step (2) is at least one of grinding and air flow pulverizing.
9. A hard carbon negative electrode material derived from coal subjected to strong oxidizing acid hydrothermal treatment obtained by the preparation method according to any one of claims 1 to 8.
10. Use of the hard carbon negative electrode material derived from strongly oxidizing acid hydrothermal treated coal as claimed in claim 9 in sodium ion batteries.
Citation Information
Cited By
Preparation method of hard carbon negative electrode material, hard carbon negative electrode material and sodium ion battery
CN121449046A